Further Evidence of the Zero-Association Between Symptoms of Insomnia and Facial Emotion Recognition—Results From a Sample of Adults in Their Late 30s - Brand, Serge; Schilling, René; Ludyga, Sebastian; Colledge, Flora; Sadeghi Bahmani, Dena; Holsboer-Trachsler, Edith; Pühse, Uwe; Gerber, Markus (Frontiers in Psychiatry, 2019)
Background: Restoring sleep is associated with favorable cognitive, emotional and behavioral adaptations. As regards the association between sleep duration and facial emotion recognition (FER), results are conflicting, and as regards the association between sleep disturbances and FER, no study has been performed so far. Accordingly, the aim of the present study was to investigate whether subjective sleep was associated with FER, along with perceived stress and mental toughness. Method: A total of 201 police officers (mean age=38.5 years, 64.2% males) took part in the present cross-sectional study. They completed questionnaires covering sociodemographic data, subjective sleep disturbances, perceived stress and mental toughness. Further, they underwent a computerized FER test, consisting of facial emotion labeling and facial emotion matching. Results: Performance of FER (accuracy, speed) was unrelated to subjective sleep disturbances. Lower FER was associated with higher age, but not to perceived stress or mental toughness. No gender differences were observed. Lower subjective sleep was associated with higher stress scores and lower scores of mental toughness. Conclusions: The pattern of results suggests that FER was not associated with sleep disturbances, understood as a proxy of sleep quality, among adults. This observation replicates those studies showing a zero-association between sleep and FER.